Early Gastric Post-Transplant Lymphoproliferative Disorder and H pylori Detection after Kidney Transplantation: A Case Report and Review of the Literature - CL Nash; LM Price; DA Stewart; F Sepandj; S Yilmaz; A Barama (Canadian Journal of Gastroenterology)
The incidence of post-transplantation lymphoproliferative disorder (PTLD) in the adult renal transplant population ranges from 0.7% to 4%. The majority of cases involve a single site and arise, on average, seven months after transplantation. Histopathology usually reveals B-cell proliferative disease and has been standardized into its own classification. Treatment modalities consist of decreased immunosuppression, eradication of Epstein-Barr virus, surgical resection, systemic chemotherapy and monoclonal antibody therapy; however, mortality remains high, typically with a short survival time. In patients who have undergone renal transplantation, approximately 10% of those with PTLDs present with gastrointestinal symptomatology and disease. Reported sites include the stomach, and small and large bowel. Very few cases of Helicobacter pylori or mucosal-associated lymphoid tissue have been described in association with PTLD. In the era of cyclosporine immunosuppression, the incidence of PTLD affecting the gastrointestinal tract may be increasing in comparison with the incidence seen with the use of older immunosuppression regimens. A case of antral PTLD and H pylori infection occurring three months after renal transplantation is presented, and the natural history and management of gastric PTLD are reviewed.